Cyclostratigraphy of Lower Permian alkaline lacustrine deposits in the Mahu Sag, Junggar basin and its stratigraphic implication - Tang, Yong; He, Wenjun; Wang, Ran; Ren, Haijiao; Jin, Zhijun; Yang, Zhuang; Zhang, Yuanyuan (Frontiers in Earth Science, 2023)
The Lower Permian Fengcheng Formation of the Mahu Sag is one of the most potentially petroliferous sequences in China, and its unique alkaline lacustrine deposits provide important information on the paleoclimate and paleoenvironment in the early Permian. However, because of the complexity of the heterogeneous lithology and sedimentary facies in lacustrine deposits, the lateral correlation of lithofacies becomes challenging. Using cyclostratigraphy, we conducted a detailed astronomical cycle analysis of the Lower Permian Fengcheng Formation in the northern Mahu Sag, established an astronomical time scale, and constructed an isochronous sedimentary framework by collating the cycles of the different wells. Nine 405-kyr long-eccentricity cycles in the Fengcheng Formation were identified, and absolute astronomical time scales were established with the anchored point at ~300 Ma in the Lower member of the Fengcheng Formation. Based on lithofacies identification, the spatio-temporal variation in the lithofacies within the Fengcheng Formation was reconstructed. The astronomical time scale has proven to be reliable, and the lithofacies distribution within the isochronal framework is effective for investigating the spatial variation of lithofacies in alkaline lacustrine deposits. Favorable dolomitic mudstones developed in the central and transitional zones, corresponding to the three long-eccentricity cycles in the middle member of the Fengcheng Formation. Tuffaceous mudstones with high potential mainly developed in the lower member of the Fengcheng Formation in the marginal zone of the Mahu Sag. This study demonstrates an approach that can be used to study lithofacies in lacustrine deposits.